RESPON PERTUMBUHAN TANAMAN DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) VARIETAS HYPOMA 1 TERHADAP PUPUK BIO URINE DAN PUPUK SP-36 - Roestandi, Dendy; Jaenudin, Amran; Purnomo, Dwi (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2023)
This study aimed to investigate the effects of different combinations of liquid organic fertilizer Bio urine and SP36 fertilizer on the growth, yield components, and overall yield of peanut plants (Arachis hypogaea L.), to identify the optimal fertilizer combination, and to determine the correlation between growth components and peanut yield. The experiment was conducted at the experimental garden of Pondok Pesantren Al-Zaytun, located in Mekarjaya Village, Gantar Subdistrict, Indramayu Regency, West Java, from August to October 2022, using a Randomized Complete Block Design (RCBD). The trial consisted of nine treatment combinations of Bio urine and SP36, each replicated three times, resulting in 27 plots. The treatments included combinations of Bio urine at 75, 100, and 125 mL/L with SP36 at 50, 100, and 150 kg/ha. The results showed that the different combinations significantly affected plant height at 14, 21, and 28 days after planting (DAP), the number of leaves at 14, 21, and 28 DAP, leaf area index at 28 DAP, number of branches at 28 DAP, root volume at 21 and 28 DAP, plant growth rate, number of pods per plant, number of filled pods per plant, wet and dry pod weight per plant, wet and dry pod weight per plot, and 100-seed dry weight. The highest dry pod yield was obtained from 125 mL/L Bio urine + 150 kg/ha SP36, which was not significantly different from 125 mL/L Bio urine + 100 kg/ha SP36, yielding 2.041 kg/plot and 2.020 kg/plot, equivalent to 3.40 t/ha and 3.37 t/ha, respectively. Significant correlations were also observed between growth components and yield: plant height at 14, 21, and 28 DAP showed a strong correlation, the number of leaves at 14, 21, and 28 DAP showed a moderate correlation, the number of branches at 28 DAP influenced dry pod weight per plot, and the number of filled pods per plant had a moderate correlation with dry pod weight per plant.